ユーラシア チョウ タイリク ノ コウゾウ ト ケイセイ ニ カンスル ワークショップ ホウコク - 金尾, 政紀; カナオ, マサキ; Kanao, Masaki (2004)
P(論文) 平成16年2月23日に国立極地研究所講堂にて,「ユーラシア(超)大陸の構造と形成に関するワークショップ」が開催された(参加者計29名).地球の進化を振り返りさらに将来の予測をする上で,かつての超大陸の離散集合の歴史を理解することは重要である.現在世界最大の面積を占めるユーラシア大陸は,アジアを核にインド・ヨーロッパ等の複数の地塊が集合して形成され,さらに数億年先には次の超大陸へ成長すると考えられている.本研究会では,ユーラシア大陸の形成過程や地殻上部マントルの構造とダイナミクスに関連した,これまでの地球科学的諸成果の発表と情報交換を目的とした.集会の前半は,典型的な大陸と大陸の衝突帯として知られているヒマラヤチベット地域の基盤地殻深部構造,また衝突帯の形成過程を解明するための個別要素法によるシミュレーションの紹介もあり,大陸衝突に伴うユーラシアの内部変形について斬新な成果が報告された.後半は,将来の超大陸形成のフロンティア地域として考えられている,西太平洋三角地帯直下の上部マントルへの吸水機構について詳しい地質学的考察がなされた.また,汎地球局所的な空間スケールでの地震波走時トモグラフィーにより,中国やオホーツク海地域の地殻上部マントルの構造と,地震活動や火山活動との関連についても最新の発表があった.最後に,重力研究からみた大陸のレオロジーやダイナミクスに関するレビュー的報告,またシベリアクラトンバイカルリフト帯の深部構造と広帯域地震観測についても紹介があった.総合討論では,超大陸の形成と分裂様式に関連して,地球深部のコア・マントル境界におけるスーパーホットプルームの形成メカニズムと,そのホットプルームの上部マントルへの伝導機構について活発な議論がなされた. A workshop on Structure and evolution of Eurasia (super-) continent" was held on 23rd February 2004, at the National Institute of Polar Research with 29 participants. This provided an opportunity to review the history of amalgamation and breakup of past super-continents in the Earth's evolution, and speculate on the possibility of future super-continent formation. The largest continent on the present Earth, Eurasia, has been formed from an assembly of several sub-continental blocks including Asia, India and Europe, etc: it is also considered to be the nucleus of a future super-continent expected to form 250 m.y. after the present. In this workshop, several interesting topics were presented regarding the formation process, structure and dynamics of Eurasia, in particular in the deep crust and upper mantle. The first half of the workshop covered structural geology, shallow and deep seismic structure, and a simulation model of the Himalaya-Tibet region, known as a typical ongoing continent-continent collision zone. Inner crustal deformation of Eurasia was demonstrated by a newly developed Discrete Element method. In the latter half of the workshop, the possibility of formation of a future super-continent in the Western Pacific Triangular Zone was introduced with geological ...